Influence of Atomic Magnetometer’s Orientation on Its Frequency Response - Zhang, Rui (Sensors (Basel, Switzerland), 2025)
Due to the high sensitivity and room temperature operation of atomic magnetometers, they have significant applications in many fields. An emerging area is the highly sensitive biomagnetic measurement in magnetically unshielded environments, which is crucial for medical diagnostics. However, in magnetically unshielded environments, atomic magnetometers often encounter situations where their orientation deviates from the optimal operating posture, and there has been insufficient research on the frequency response information of atomic magnetometers under such conditions. Addressing this issue, we modeled the atomic magnetometer using the Bloch equations and obtained approximate analytical solutions for the frequency response of the atomic magnetometer in different orientations, which were experimentally verified using a Bell–Bloom magnetometer. We found that although the magnetic resonance spectrum of the magnetometer is influenced by the orientation of the magnetometer, the frequency response of the magnetometer can be made independent of its orientation by judiciously selecting the demodulation components used for the operation of the magnetometer. This finding is important for biomagnetic detection in magnetically unshielded environments where orientation-robust measurements of AC magnetic signals are required.